Trzy koncepcje bytu/przedmiotu - Wojtysiak, Jacek (Filozofia Nauki, 1997)
The aim of this article is to present the main results of investigations in the domain of object theory, carried out by the representants of three Polish philosophical schools: M. Borowski (the Lvov-Warsaw School), R. Ingarden (the phenomenological Lvov-Cracow School), and M. Krapiec (the neo-tomist Lublin School).